Synthesis and physico-chemical properties of esters of 2- (4-R-5- (5-bromothiophen-2-yL)-4H-1,2,4-triazol-3-ylthio) acetic acids - Salionov, V. O.; Vasylyev, D. А.; Novik, Y. V.; Саліонов, Володимир Олександрович; Васильєв, Денис Андрійович (X. : НФаУ, 2021)
Aim. Therefore, we considered it expedient to synthesize a number of esters of 2-(4-R-5-(5- bromothiophen-2-yl)-4H-1,2,4-triazol-3-ylthio) acetic acids and to investigate their physicochemical properties.